Starch-halloysite nanocomposites containing nisin: Characterization and inhibition of Listeria monocytogenes in soft cheese. (May 2016) - Meira, Stela Maris Meister; Zehetmeyer, Gislene; Scheibel, Jóice Maria; Werner, Júlia Orlandini; Brandelli, Adriano
Abstract: Starch/halloysite/nisin nanocomposite films were developed as active antimicrobial packaging. Nanocomposites without nisin and control films (containing starch and glycerol only) were also prepared. Scanning electron microscopy revealed that all samples were homogeneous, halloysite nanotubes (HNT) were dispersed in starch matrix, and film surfaces denoted aggregates as higher amount of nisin was added. X-ray diffraction spectra displayed alterations in typical starch peaks after HNT and nisin incorporation, indicating a decrease in polymer crystallization. Mechanical properties were improved when HNT was incorporated, but inferior values of Young modulus and tensile strength were obtained with nisin addition. Thermal stability decreased for bionanocomposites containing nisin, which showed T max values about 20 °C lower than films without nisin. The antimicrobial activity was tested against Listeria monocytogenes, Clostridium perfringens and Staphylococcus aureus in skimmed milk agar and all microorganisms were inhibited by nanocomposites containing nisin. These active films were applied on Minas Frescal cheese surface previously inoculated with L. monocytogenes . After 4 days, antimicrobial nanocomposite films with 2 g/100 g nisin significantly reduced the initial counts of the bacterium and those with 6 g/100 g nisin completely inhibited L. monocytogenes . Results showed that nisin supported in starch/halloysite films can be an active and useful barrier to control food contamination. Highlights: Starch nanocomposite films containing nanoclay and nisin were prepared. Morphological, mechanical and thermal properties of the films were determined. Nanocomposite films containing nisin inhibited Listeria monocytogenes, Staphylococcus aureus and Clostridium perfringens . The active films inhibited L. monocytogenes growth in Minas Frescal cheese.